2016
DOI: 10.1159/000453190
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Long Non-Coding RNAs Act as Biomarkers for Predicting 131I Uptake and Mortality in Papillary Thyroid Cancer Patients with Lung Metastases

Abstract: Purpose: The aims of the current study were to explore plasma lncRNAs as a novel biomarker panel for the diagnosis of non-131I-avid lung metastases of PTC and to investigate the plasma lncRNA expression levels associated with survival in PTC patients with lung metastases. Methods: The expression of lncRNAs was examined using an lncRNA microarray chip. The lncRNAs with the most significant difference in expression between PTC patients with non-131I-avid lung metastases and PTC patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…In favor of this prospect, although no lncRNAs were reported in the bodily fluids of patient with OC, recent studies have identified elevated plasma lncRNA levels in patients with other cancer types such as non-small-cell lung cancer [83], hepatocellular carcinoma [84], thyroid cancer with lung metastases [85], esophageal squamous cell carcinoma [86], and renal cell carcinoma [87].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…In favor of this prospect, although no lncRNAs were reported in the bodily fluids of patient with OC, recent studies have identified elevated plasma lncRNA levels in patients with other cancer types such as non-small-cell lung cancer [83], hepatocellular carcinoma [84], thyroid cancer with lung metastases [85], esophageal squamous cell carcinoma [86], and renal cell carcinoma [87].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Other factors are also associated with an unfavorable prognosis including age (>45 years), male sex, histology (tall cell variant histology), extrathyroidal extension (EXE), larger tumor size, stage III and IV disease, resistance to radioiodine therapy, distant metastasis, positive family history, and the BRAF V600E mutation [6, 7, 9, 13-19]. Therefore, the underlying inherent molecular mechanism of the aggressiveness and progression of PTC has great significance in the ability to understand the biological basis for the improvement in clinical outcomes [20-22]. …”
Section: Introductionmentioning
confidence: 99%
“…PTC’s pathogenesis is still not fully understood [1, 2]. Existing studies suggest that radiation and genetic susceptibility contribute to the initiation and progression of PTC [6-11]. The molecularly-targeted therapy is important for better and efficient treatment of PTC [8-13].…”
Section: Introductionmentioning
confidence: 99%